Lithium ion battery

By forming an ion conductor modification layer on the surface of the positive electrode active material layer of the lithium-ion battery, the problems of high-nickel ternary positive electrode material being easily oxidized and crystal structure collapse during the cycle process are solved, and the cycle stability and energy density of the battery are improved.

CN119627036APending Publication Date: 2025-03-14AESC DYNAMICS TECHNOLOGY (ORDOS) LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411687389.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The high-nickel ternary positive electrode material is prone to oxidation during the cycle, resulting in increased electrolyte consumption and internal resistance. The collapse of the crystal structure leads to nickel ion migration and negative electrode SEI damage, resulting in rapid capacity decay.

Method used

A modified layer is formed on the surface of the positive electrode active material layer. The modified layer includes ionic conductors, such as Li1+aAaD2-a(PO4)3, Li3xLa2/3-xTiO3 or lithium phospho-oxygen, and is prepared by magnetron sputtering and other methods, with a thickness ranging from 2nm to 1000nm.

Benefits of technology

Effectively prevent the electrolyte from being oxidized, stabilize the interface between the positive electrode and the electrolyte, reduce the loss of active lithium caused by side reactions, and improve the circulation stability and energy density of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627036A_ABST
    Figure CN119627036A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery. The lithium ion battery comprises a positive electrode and a negative electrode, the positive electrode comprises a positive electrode current collector, a positive electrode active material layer and a modification layer. The positive electrode active material layer is at least located on the surface of one side of the positive electrode current collector and comprises a positive electrode active material, the structural general formula of the positive electrode active material is LixNiyMnzMmO0. 5x + 1.5 y + 1.5 z + 1.5 m, x is larger than or equal to 0.9 and smaller than or equal to 1.1, y + z is larger than or equal to 0.8 and smaller than or equal to 1.1, y is larger than or equal to z, m is larger than or equal to 0 and smaller than or equal to 0.2, and M is at least one of Fe, Ti, Co, Cr, V, Cu, Zn, Zr, Al and Nb. The modification layer is located on the surface of the side, away from the positive electrode current collector, of the positive electrode active material layer, the modification layer comprises an ion conductor, the ion conductor is at least one of Li < 1 + a > A D < 2-a > (PO4) 3, Li < 3 > x La < 2 / 3-x > TiO3, Li < 7 > La < 3 > Zr < 2 > O < 12 > and lithium phosphorus oxygen nitrogen, A is at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, and D is at least one of Ti, Ge, Zr, Sn or Hf, 0 lt; a is less than or equal to 1, 0.05 lt; xlt; and 0.16.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery. Background Art

[0002] Lithium-ion batteries are developing rapidly in the fields of electric vehicles and large-scale energy storage, and consumers have also put forward higher requirements for the energy density of lithium-ion batteries. Increasing the operating voltage of lithium-ion batteries is an effective means to increase the energy density of batteries. Therefore, developing positive electrode materials with high specific capacity is an important way to achieve high specific energy lithium-ion batteries. The specific capacity of lithium-ion batteries using high-nickel-content nickel-cobalt-manganese-oxide (high-nickel ternary) positive electrode materials can reach 220mAh / g, which significantly improves the energy density of the battery.

[0003] Although high-nickel ternary positive electrode materials show broad application prospects, their cycle stability faces severe challenges. This is mainly reflected in the following two aspects: First, the traditional carbonate-based electrolyte is easily oxidized by the high-nickel ternary positive electrode with a high oxidation state during the cycle, resulting in irreversible oxidative decomposition reactions on the surface of the positive electrode material. This reaction will lead to continuous consumption of the electrolyte and gradually increase the internal resistance of the battery with the increase in the number of cycles. Secondly, a higher degree of delithiation will aggravate the collapse of the positive electrode crystal structure, causing the dissolved nickel ions to migrate to the negative electrode surface through the electrolyte, and reduce and deposit on the negative electrode side, thereby destroying the negative electrode SEI (Solid Electrolyte Interphase), catalyzing the reduction reaction of the electrolyte, causing an increase in local polarization, leading to lithium loss, and thus causing problems such as rapid capacity decay.

[0004] Therefore, the high nickel positive electrode in the prior art has the problem of easy oxidation of electrolyte and easy collapse of crystal structure, which will lead to a decrease in battery rate performance and a shortened cycle life. Summary of the invention

[0005] The present invention aims to provide a lithium ion battery so as to at least solve or alleviate some of the problems existing in the prior art.

[0006] The present invention provides a lithium ion battery, comprising a positive electrode and a negative electrode. The positive electrode comprises: a positive electrode current collector, a positive electrode active material layer and a modified layer. The positive electrode active material layer is located at least on one side of the positive electrode current collector, and the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material has a general structural formula of Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m, wherein 0.9≤x≤1.1, 0.8≤y+z≤1.1, y≥z, 0≤m≤0.2, and M is at least one of Fe, Ti, Co, Cr, V, Cu, Zn, Zr, Al, and Nb. The modified layer is located on the surface of the positive electrode active material layer away from the positive electrode current collector, and the modified layer includes an ion conductor, and the ion conductor is Li 1+a A a D 2-a (PO 4 ) 3 , Li 3x La 2 / 3-x TiO 3 , Li 7 La 3 Zr 2 O 12 and at least one of lithium phosphorus, oxygen and nitrogen, wherein A is at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, D is at least one of Ti, Ge, Zr, Sn or Hf, 0 <a≤1,0.05<x<0.16。

[0007] In the lithium-ion battery of an optional technical solution, the thickness of the modified layer is greater than or equal to 2 nm and less than or equal to 1000 nm.

[0008] In the lithium-ion battery of an optional technical solution, the thickness of the modified layer is greater than or equal to 2 nm and less than or equal to 100 nm.

[0009] In the lithium-ion battery of an optional technical solution, the ion conductor is lithium phosphorus oxygen nitrogen.

[0010] In the lithium ion battery of an alternative technical solution, the modification layer is formed by deposition on the surface of the positive electrode active material layer attached to the positive electrode collector.

[0011] In the lithium-ion battery of the optional technical solution, the modification layer is prepared by at least one of vacuum evaporation, ion plating, thermal chemical vapor deposition, plasma chemical vapor deposition, organic metal chemical vapor deposition, metal chemical vapor deposition, radio frequency sputtering, magnetron sputtering or reactive sputtering.

[0012] In the lithium-ion battery of an optional technical solution, the modified layer is prepared by magnetron sputtering.

[0013] In the lithium-ion battery of the optional technical solution, the nickel content K and the transition metal content Q in the positive electrode active material layer satisfy the following mathematical relationship: nickel content K / transition metal content Q≥0.8.

[0014] In the lithium-ion battery of the optional technical solution, the total amount W of the positive electrode active material layer and the positive electrode active material content S satisfy the following mathematical relationship: 0.5≤positive electrode active material content S / total amount W of the positive electrode active material layer≤1.

[0015] In the lithium-ion battery of the optional technical solution, the lithium ion conductivity of the ion conductor is greater than 10 -6 S / cm, and the electronic conductivity is less than 10 -9 S / cm. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The schematic diagram of the structure of the positive electrode of the lithium-ion battery in the embodiment of the present invention is shown.

[0017] Reference numerals: positive electrode 10 , positive electrode current collector 1 , positive electrode active material layer 2 , modified layer 3 , positive electrode basic structure 101 . DETAILED DESCRIPTION

[0018] First of all, it should be noted that the composition, working principle, characteristics and advantages of the lithium-ion battery according to the present invention will be described below in an exemplary manner, but it should be understood that all descriptions are given for illustration only and should not be construed as forming any limitation on the present invention.

[0019] In addition, for any single technical feature described or implied in the embodiments mentioned in this document, or any single technical feature displayed or implied in the accompanying drawings, the present invention still allows continued arbitrary combination or deletion between these technical features (or their equivalents) without any technical obstacles, thereby obtaining more other embodiments of the present invention that may not be directly mentioned in this document.

[0020] <Positive electrode of lithium-ion battery 10>

[0021] Figure 1 FIG. 1 shows a schematic diagram of the structure of the positive electrode 10 of a lithium-ion battery in an embodiment of the present invention. Figure 1 As shown, the positive electrode 10 includes: a positive electrode collector 1, a positive electrode active material layer 2 and a modified layer 3. The positive electrode active material layer 2 is located on one side of the positive electrode collector 1. The modified layer 3 is located on the side of the positive electrode active material layer 2 away from the positive electrode collector 1.

[0022] Although in the illustrated embodiment, the positive electrode active material layer 2 is only shown to be located on one side of the positive electrode current collector 1. However, in other embodiments, the positive electrode active material layer 2 may be located on both sides of the positive electrode current collector 1. Figure 1 The thicknesses of the positive electrode collector 1 , the positive electrode active material layer 2 and the modified layer 3 shown in the figure are for illustration only and do not represent actual sizes, nor do they constitute limitations to the present invention.

[0023] The positive electrode collector 1 of the positive electrode 10 can be made of aluminum foil. Aluminum has good electrical conductivity, chemical stability, low cost and relatively light weight. Aluminum as the positive electrode collector 1 also has good corrosion resistance and is suitable for use with positive electrode materials to maintain the electrochemical stability of the battery. Of course, the material selection of the positive electrode collector 1 is not limited to this. In some embodiments, any one of Pt, Au, Cu, Ag, Mo, Ni, and stainless steel metal materials can also be selected.

[0024] The positive electrode active material layer 2 includes a positive electrode active material, and the positive electrode active material has a general structural formula of Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m , wherein 0.9≤x≤1.1, 0.8≤y+z≤1.1, y≥z, 0≤m≤0.2, and M is at least one of Fe, Ti, Co, Cr, V, Cu, Zn, Zr, Al and Nb.

[0025] Preferably, the nickel content K in the positive electrode active material layer 2 and the transition metal content Q satisfy the following mathematical relationship: nickel content K / transition metal content Q ≥ 0.8. More preferably, the nickel content K in the positive electrode active material layer 2 and the transition metal content Q satisfy the following mathematical relationship: nickel content K / transition metal content Q ≥ 0.9. A positive electrode with a higher nickel content K has a higher specific capacity, which is beneficial to improving the energy density of the battery. Of course, it can be understood that the present application can also be applied to the case where the proportion of nickel content K to transition metal content Q is less than 0.8.

[0026] It should be noted that the positive electrode active material layer 2 may include not only the positive electrode active material (i.e., Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m ), and may also include other types of positive electrode active materials. In some embodiments described herein, the positive electrode active material layer 2 includes a positive electrode active material, that is, a positive electrode active material having a general structural formula of Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m In other embodiments, the positive electrode active material layer 2 comprises a positive electrode active material having a general structural formula of Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m positive electrode active material, and a second type of positive electrode active material.

[0027] The positive electrode active material layer 2 generally may include substances such as a conductive agent and a binder. The type of the conductive agent may be selected from one or more of graphite, graphene, acetylene black, carbon black, carbon fiber, and carbon nanotube. The type of the binder may be selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), nitrile rubber (NBR), styrene-ethylene-butylene-styrene copolymer (SEBS), styrene-butadiene-styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, and lithium alginate.

[0028] Preferably, between the total amount W of the positive electrode active material layer 2 and the content S of the positive electrode active material (i.e., Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m ), the following mathematical relationship is satisfied: 0.5 ≤ content S of the positive electrode active material / total amount W of the positive electrode active material layer 2 ≤ 1.

[0029] The modification layer 3 includes an ion conductor, and the ion conductor is Li 1+a A a D 2-a (PO 4 ) 3 、Li 3x La 2 / 3-x TiO 3 、Li 7 La 3 Zr 2 O 12 and at least one of lithium phosphorus oxynitride, where A is at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y, or La, D is at least one of Ti, Ge, Zr, Sn, or Hf, 0 < a ≤ 1, 0.05 < x < 0.16. Preferably, the lithium ion conductivity of the ion conductor is greater than 10 -6 S / cm, and the electronic conductivity is less than 10 -9 S / cm. The ion conductor generally should be in a solid state within the battery operating range.

[0030] There is a modified layer 3 including an ion conductor on the surface of the positive electrode active material layer 2, which allows ions to flow but prevents electrons from flowing, thereby effectively preventing electrons in the positive electrode active material layer 2 from flowing to the electrolyte. This helps to avoid oxidation of the electrolyte, stabilize the interface between the positive electrode 10 and the electrolyte, reduce the loss of active lithium caused by side reactions, and thus improve the cycle of the lithium ion battery. At the same time, the modified layer 3 has a good lithium ion transmission capacity, which can prevent the local enrichment of lithium ions on the surface of the positive electrode particles due to insufficient diffusion channels, thereby reducing the amplitude of the impedance increase. In addition, since the modified layer 3 basically only conducts lithium ions, coating it at the interface between the positive electrode active material layer 2 and the electrolyte can also prevent the nickel ions in the positive electrode active material layer 2 from dissolving into the electrolyte.

[0031] For the positive electrode active material layer 2 with a higher nickel content K, the degree of lithium removal will be higher. In the state of high lithium removal, the oxygen ions (O 2- ) may be oxidized to a higher valence state, or even become free radical oxygen or oxygen precipitate, thereby oxidizing the electrolyte. By coating the modified layer 3 at the interface of the positive electrode active material layer 2 and the electrolyte, a stable interface layer can be constructed to limit the process of oxygen precipitation. This not only helps to maintain the stability of the positive electrode crystal structure and reduce the risk of crystal structure collapse, but also can improve the stability of the interface between the positive electrode 10 and the electrolyte, thereby achieving a stable cycle of the positive electrode 10.

[0032] It is worth noting that, since the modified layer 3 is formed on the surface of the positive electrode active material layer 2 , it will not affect the ion and electron transport inside the positive electrode active material layer 2 , which is conducive to maintaining good kinetic performance.

[0033] In some embodiments, the thickness of the modified layer 3 is greater than or equal to 2nm and less than or equal to 1000nm. Preferably, the thickness of the modified layer 3 is greater than or equal to 2nm and less than or equal to 100nm. Through the modified layer 3 of appropriate thickness, the modified layer 3 has good lithium ion transmission ability, which alleviates the problem of easy collapse of the positive electrode crystal structure caused by the uneven distribution of lithium ions in the positive electrode particles, which is conducive to maintaining good dynamic performance of the battery as a whole and improving the capacity retention rate of the cycle. Of course, the selection range of the thickness of the above-mentioned modified layer 3 is only an optional technical solution and does not constitute a limitation of the present invention. It can be understood that as long as the modified layer 3 is provided on the surface of the positive electrode active material layer 2, the problem of easy collapse of the positive electrode crystal structure and the oxidation electrolyte of the high-nickel positive electrode material can be alleviated to a certain extent.

[0034] In some embodiments, the modified layer 3 is formed by deposition on the surface of the positive electrode active material layer 2 attached to the positive electrode current collector 1, that is, the modified layer 3 is formed by deposition on the surface of the unmodified positive electrode basic structure 101. Optionally, the modified layer 3 is prepared by at least one of vacuum evaporation, ion plating, thermal chemical vapor deposition, plasma chemical vapor deposition, organic metal chemical vapor deposition, metal chemical vapor deposition, radio frequency sputtering, magnetron sputtering or reactive sputtering.

[0035] Preferably, the modified layer 3 is prepared by magnetron sputtering. During the deposition process of the modified layer 3, magnetron sputtering restrains the ions excited by the sputtering target by enhancing the magnetic field, so that they are uniformly deposited on the surface of the positive electrode basic structure 101, thereby ensuring that the prepared ion conductor modified layer 3 has a uniform thickness and stable composition. In addition, the cost of preparing the modified layer 3 by magnetron sputtering is more controllable, which is conducive to the large-scale preparation of the modified layer 3.

[0036] <Lithium-ion battery>

[0037] The embodiment of the present invention also provides a lithium ion battery, which includes the positive electrode 10 described above. Due to the use of the positive electrode 10 with a higher nickel content K, the lithium ion battery has a higher energy density. At the same time, the positive electrode 10 with the modified layer 3 can alleviate the problems of the electrolyte being oxidized by the high-nickel positive electrode and the nickel ions destroying the negative electrode SEI film and then reducing and depositing on the negative electrode, so that the performance of the lithium ion battery, such as the rate performance and cycle life, can be maintained at a good level.

[0038] In some embodiments, the lithium-ion battery includes a positive electrode 10, a negative electrode, a separator, a package and an electrolyte. The positive electrode 10, the separator and the negative electrode are stacked in sequence to form a positive and negative electrode stack separated by the separator (i.e., a bare cell). The bare cell is packaged inside the package together with the electrolyte.

[0039] The technical scheme of the present invention is described in detail below through specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0040] The compositions of the modified layers of different groups of embodiments and comparative examples are specifically referred to Table 1.

[0041] [Example 1]

[0042] Embodiment 1 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer 3 is lithium phosphorus oxygen nitrogen. The preparation method of the modification layer 3 is magnetron sputtering. The thickness of the modification layer 3 is 5nm.

[0043] [Example 2]

[0044] Embodiment 2 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer 3 is lithium phosphorus oxygen nitrogen. The preparation method of the modification layer 3 is magnetron sputtering. The thickness of the modification layer 3 is 8nm.

[0045] [Example 3]

[0046] Embodiment 3 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer 3 is lithium phosphorus oxygen nitrogen. The preparation method of the modification layer 3 is magnetron sputtering. The thickness of the modification layer 3 is 100nm.

[0047] [Example 4]

[0048] Embodiment 4 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer 3 is lithium phosphorus oxygen nitrogen. The preparation method of the modification layer 3 is magnetron sputtering. The thickness of the modification layer 3 is 1000nm.

[0049] [Example 5]

[0050] Embodiment 5 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modified layer 3 is Li 7 La 3 Zr 2 O 12 The modification layer 3 is prepared by magnetron sputtering and has a thickness of 5 nm.

[0051] [Example 6]

[0052] Embodiment 6 provides a lithium ion battery, including a positive electrode 10 and a negative electrode. The positive electrode 10 includes a positive electrode active material layer 2 and a modified layer 3 covering the surface of the positive electrode active material layer 2. The positive electrode active material layer 2 includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modified layer 3 is Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The modification layer 3 is prepared by magnetron sputtering and has a thickness of 5 nm.

[0053] [Comparative Example 1]

[0054] Comparative Example 1 provides a lithium ion battery, including a positive electrode and a negative electrode. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The positive electrode does not include the modified layer 3.

[0055] [Comparative Example 2]

[0056] Comparative Example 2 provides a lithium ion battery, including a positive electrode and a negative electrode. The positive electrode includes a positive electrode active material layer and a modified layer covering the surface of the positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer is lithium phosphorus oxygen nitrogen. The preparation method of the modification layer is magnetron sputtering. The thickness of the modification layer is 2000nm.

[0057] [Comparative Example 3]

[0058] Comparative Example 3 provides a lithium ion battery, including a positive electrode and a negative electrode. The positive electrode includes a positive electrode active material layer and a modified layer covering the surface of the positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modified layer is Li 7 La 3 Zr 2 O 12 The modification layer is prepared by magnetron sputtering and has a thickness of 2000 nm.

[0059] [Comparative Example 4]

[0060] Comparative Example 4 provides a lithium ion battery, including a positive electrode and a negative electrode. The positive electrode includes a positive electrode active material layer and a modified layer covering the surface of the positive electrode active material layer. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The structural formula of the positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The conductive agent is acetylene black. The binder is polyvinylidene fluoride. The modification layer is aluminum oxide. The preparation method of the modification layer is magnetron sputtering. The thickness of the modification layer is 5 nm.

[0061] Table 1. Composition of modified layers of different groups of examples and comparative examples

[0062]

[0063]

[0064] According to the positive electrodes of lithium ion batteries provided in the above-mentioned embodiments 1-6 and comparative examples 1-4, lithium ion batteries are prepared respectively. As a specific example, the preparation method of the lithium ion battery is as follows.

[0065] (1) Preparation of positive electrode

[0066] The positive electrode active material (LiNi 0.8 Co 0.1 Mn 0.1 O 2), conductive agent (acetylene black), and binder (polyvinylidene fluoride) are fully stirred and mixed in an N-methylpyrrolidone solvent system at a mass ratio of 95:3:2, and then coated on a positive electrode collector (aluminum foil), dried, and cold pressed to obtain an unmodified positive electrode basic structure. The desired composite positive electrode is obtained by constructing a modified layer on the unmodified positive electrode basic structure.

[0067] (2) Preparation of negative electrode:

[0068] The negative electrode active material (graphite), conductive agent (acetylene black), binder (styrene-butadiene rubber), and thickener (sodium carbon methyl cellulose) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 96:2:1:1, and then coated on a negative electrode collector (copper foil), dried, and cold pressed to obtain a negative electrode.

[0069] (3) Preparation of diaphragm

[0070] A 9 μm polyethylene was selected as a base film, and a 3 μm thick nano-aluminum oxide coating was coated on the base film to obtain a diaphragm.

[0071] (4) Preparation of lithium-ion batteries

[0072] The positive electrode, separator and negative electrode prepared above are stacked in sequence, so that the separator is placed between the positive electrode and the negative electrode to play an isolating role, and the bare battery cell is stacked. The bare battery cell is loaded into the aluminum plastic film, and then baked at 80°C to remove water, and then the corresponding electrolyte is injected and sealed. After that, the finished soft-package lithium-ion battery is obtained through the processes of standing, hot and cold pressing, formation, clamping, and capacity division.

[0073] The lithium ion batteries prepared by using the positive electrodes 10 provided in the above-mentioned Examples 1-6 and Comparative Examples 1-4 were subjected to performance tests. The methods for various performance tests are as follows.

[0074] (1) DCR test at 50% SOC

[0075] Adjust the temperature of the incubator to a constant 25°C. After standing for 10 minutes, charge the battery to 4.25V at a constant current of 0.33C, and then charge at a constant voltage of 4.25V until the current drops to 0.05C. After charging is completed, stand for 10 minutes, and then discharge to 2.8V at a constant current of 0.33C to measure the theoretical capacity of the battery. Subsequently, charge to 4.25V at a constant current of 0.33C, and then charge to a current of 0.05C at a constant voltage of 4.25V. After charging, stand for 10 minutes, and then discharge at 0.33C to adjust the battery capacity to 50% SOC. After standing for 1 hour, record the initial voltage V1 of the battery. Next, discharge at a current of 4C I0 for 30 seconds, and record the battery voltage V2 after discharge.

[0076] The DC resistance (DCR) of the battery at 50% SOC is calculated according to the following formula: DCR (mΩ) = (V 1 -V 2 ) / I 0 .

[0077] (2) Capacity retention test after 800 cycles at 25°C

[0078] At 25°C, the lithium-ion battery was tested as follows: first, it was charged to 4.25V at a constant current of 1C, and then charged at a constant voltage of 4.25V until the current dropped to less than 0.05C. After charging, it was left for 10 minutes, and then discharged to 2.8V at a constant current of 1C, and the discharge capacity at this time was recorded as the discharge capacity of the first cycle. The battery was tested for multiple cycles under this charge and discharge condition, and the discharge capacity of the 800th cycle was measured.

[0079] The capacity retention rate of the battery after 800 cycles was calculated according to the following formula: Capacity retention rate (%) = (discharge capacity of the 800th cycle / discharge capacity of the first cycle) × 100%.

[0080] (3) 60℃ high temperature storage DCR growth rate test

[0081] The formed battery was charged at room temperature with a constant current and constant voltage of 1C to the cut-off voltage, and then discharged at a current of 1C to 50% SOC. Subsequently, the DC internal resistance (DCR) was tested by discharging at a current of 4C for 30 seconds, and recorded as DCR 0 Then continue to discharge at 1C current to the cut-off voltage, and then charge at 1C constant current and constant voltage to the cut-off voltage, and store at 60℃ for 90 days. After storage, wait for the lithium-ion battery to cool to room temperature, and then test the DCR under the same conditions, recorded as DCR 90 The DCR storage growth rate is (DCR 90 / DCR 0 -1)*100%. For lithium nickel cobalt manganese oxygen / silicon-graphite batteries, the charge and discharge cut-off voltage range is 2.8V to 4.25V.

[0082] The lithium-ion batteries prepared by using the positive electrodes provided by the above-mentioned Examples 1-6 and Comparative Examples 1-4 were subjected to performance tests in the manner described above. The test results are as follows.

[0083] Table 2 Lithium ion battery performance test results of Examples 1-6 and Comparative Examples 1-4

[0084]

[0085]

[0086] The data in Table 2 will be analyzed below.

[0087] By comparing the test results of Examples 1-6, Comparative Examples 2-4 (with a modified layer) and Comparative Example 1 (without a modified layer), it can be seen that forming a modified layer on the positive electrode can effectively improve the room temperature cycle performance of the battery (the capacity retention rate of 800 cycles at 25°C is improved) and high temperature storage stability (the DCR growth rate at 60°C high temperature storage is reduced).

[0088] By comparing the test results of Examples 1-4 (modified layer thickness is appropriate) and Comparative Example 2 (modified layer thickness is too large), as well as the test results of Example 5 (modified layer thickness is appropriate) and Comparative Example 3 (modified layer thickness is too large), it can be seen that the thickness of the modified layer will affect the impedance of the battery. When the thickness of the modified layer exceeds 1000nm, the impedance of the battery increases significantly (the DCR of 50% SOC at 25℃ increases), and the room temperature cycle performance of the battery deteriorates (the capacity retention rate after 800 cycles at 25℃ decreases).

[0089] By comparing the test results of Examples 1, 5-6 (the modified layer is an ion conductor) and Comparative Example 4 (the modified layer does not conduct lithium ions), it can be seen that the modified layer is an ion conductor, which is beneficial to reducing the impedance of the battery (the DCR of 50% SOC at 25°C is reduced), and can make the room temperature cycle performance of the battery have a more obvious improvement (the capacity retention rate of 800 cycles at 25°C is improved).

[0090] Compare Example 1 (the modified layer is lithium phosphorus oxygen nitrogen) and Examples 5-6 (the modified layers are Li 7 La 3 Zr 2 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 ) test results show that the use of lithium phosphorus oxygen nitrogen as the modification layer is more conducive to improving the battery's room temperature cycle performance (capacity retention rate after 800 cycles at 25°C) and high temperature storage stability (DCR growth rate at 60°C high temperature storage is reduced). This is mainly due to the fact that lithium phosphorus oxygen nitrogen is more 7 La 3 Zr 2 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Thermodynamically more stable, lithium phosphorus oxygen nitrogen has better chemical stability and antioxidant properties, and is less likely to decompose or react with other materials in the working environment of the battery.

[0091] By comparing the test results of Examples 1-3 (the thickness of the modified layer 3 is relatively smaller) and Example 4 (the thickness of the modified layer 3 is relatively larger), it can be seen that a relatively smaller thickness of the modified layer is more conducive to improving the room temperature cycle performance of the battery (the capacity retention rate of 800 cycles at 25°C is improved), and is conducive to reducing the impedance of the battery (the DCR of 50% SOC at 25°C is reduced).

[0092] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: It comprises a positive electrode and a negative electrode, wherein the positive electrode comprises: Positive electrode current collector; The positive electrode active material layer is located at least on one side of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material has a general structural formula of Li x Ni y Mn z M m O 0.5x+1.5y+1.5z+1.5m , wherein 0.9≤x≤1.1, 0.8≤y+z≤1.1, y≥z, 0≤m≤0.2, and M is at least one of Fe, Ti, Co, Cr, V, Cu, Zn, Zr, Al and Nb; The modified layer is located on the surface of the positive electrode active material layer on the side away from the positive electrode current collector, and the modified layer includes an ion conductor, and the ion conductor is Li 1+a A a D 2-a (PO4)3、Li 3x La 2 / 3-x TiO3、Li7La3Zr2O 12 and at least one of lithium phosphorus, oxygen and nitrogen, wherein A is at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, D is at least one of Ti, Ge, Zr, Sn or Hf, 0 <a≤1,0.05<x<0.16。 2. The lithium-ion battery according to claim 1, characterized in that: The thickness of the modified layer is greater than or equal to 2 nm and less than or equal to 1000 nm.

3. The lithium-ion battery according to claim 2, characterized in that: The thickness of the modified layer is greater than or equal to 2 nm and less than or equal to 100 nm.

4. The lithium-ion battery according to claim 1, characterized in that: The ion conductor is lithium phosphorus oxygen nitrogen.

5. The lithium-ion battery according to claim 1, characterized in that: The modified layer is formed by deposition on the surface of the positive electrode active material layer attached to the positive electrode current collector.

6. The lithium-ion battery according to claim 1, characterized in that: The modified layer is prepared by at least one of vacuum evaporation, ion plating, thermal chemical vapor deposition, plasma chemical vapor deposition, organic metal chemical vapor deposition, metal chemical vapor deposition, radio frequency sputtering, magnetron sputtering or reactive sputtering.

7. The lithium ion battery according to claim 6, characterized in that: The modified layer is prepared by magnetron sputtering.

8. The lithium-ion battery according to claim 1, characterized in that: The nickel content K and the transition metal content Q in the positive electrode active material layer satisfy the following mathematical relationship: Nickel content K / transition metal content Q≥0.

8.

9. The lithium ion battery according to claim 1, characterized in that: The total amount W of the positive electrode active material layer and the content S of the positive electrode active material satisfy the following mathematical relationship: 0.5≤content S of the positive electrode active material / total amount W of the positive electrode active material layer≤1.

10. The lithium ion battery according to claim 1, characterized in that: The lithium ion conductivity of the ion conductor is greater than 10 -6 S / cm, and the electronic conductivity is less than 10 -9 S / cm.

Citation Information

Patent Citations

  • Positive pole, preparation method thereof and lithium-ion battery

    CN103022415A

  • Lithium ion battery

    CN115020638A

  • Lithium ion battery and positive pole piece thereof

    CN115602786A

  • Electrode positive pour generateur electrochimique lithium-ion

    FR3019168A1